The oncogenic role of MUC12 in RCC progression depends on c‐Jun/TGF‐β signalling. Issue 15 (28th June 2020) - Gao, Sheng‐Lin; Yin, Rui; Zhang, Li‐Feng; Wang, Si‐Min; Chen, Jia‐Sheng; Wu, Xing‐Yu; Yue, Chuang; Zuo, Li; Tang, Min
Abstract: Renal cell carcinoma (RCC) is a common kidney cancer worldwide. Even though current treatments show promising therapeutic effectiveness, metastatic RCC still has limited therapeutic options so that novel treatments were urgently needed. Here, we identified that MUC12 was overexpressed in RCC patients and served as poor prognostic factor for RCC progression. Overexpression of MUC12 increased RCC cell growth and cell invasion while deficiency of MUC12 exerted opposite effects on RCC cells. Mechanistic dissection demonstrated that MUC12‐mediated RCC cell growth and cell invasion were dependent of TGF‐β1 signalling because they could be blocked in the presence of TGF‐β1 inhibitor. Moreover, the regulation of TGF‐β1 by MUC12 relied on the transactivation of c‐Jun. MUC12 promoted the recruitment of c‐Jun on the promoter of TGF‐β1, leading to its transcription. Importantly, knockdown of c‐Jun also attenuated MUC12‐mediated TGF‐β1 induction and RCC cell invasion. In summary, our study defines the role of MUC12 in RCC progression and provides rational to develop novel targeted therapy to battle against RCC.